Keikutsertaan menjadi akseptor KB ditinjau dari aspek sosial budaya dan dukungan keluarga - Nopita Yanti Sitorus; R Maimunah (Holistik Jurnal Kesehatan, 2020)
Socio-cultural and family  aspects among female participation in family planningBackground: The family planning program is one way to suppress population growth. However, the phenomenon in some communities regarding family planning is that there are values, culture and norms that have not been able to accept birth control programs and think that family planning is not in accordance with the values believed so that the family also does not provide support.Purpose: To analyze the socio-cultural relationship and family support with family planning participation.Method: A quantitative study with a cross sectional approach. The research was conducted in the area of public Health Centre (Puskesmas) Kota Datar, Tandem Hulu I Village. The study population was 1711 people and the sample was 324 responden taken by simple random sampling. Data analysis used univariate analysis, bivariate analysis with chi-square test at the 95% confidence level ( = 0.05).Results: The  socio-culture and family support were related to family planning participation in the working area of the Public Health Centre (Puskesmas) Kota Datar, Tandem Hulu I Village, Hamparan Perak District, Deli Serdang Regency, p <0.05.Conclusion: The wife who do not get support socio-culture and get support from family tend to use contraceptives and wifes who has support socio-culture and do not get support from their husbands tend not to use contraceptives.Keywords: Socio-culture; Family support; Participation; Female; Family planningPendahuluan : Program KB merupakan salah satu cara untuk menekan pertumbuhan penduduk. Namun, fenomena pada sebagian masyarakat tentang KB yaitu adanya nilai, budaya dan norma yang belum dapat menerima program pengaturan kelahiran dan menganggap KB tidak sesuai dengan nilai-nilai yang diyakini sehingga keluarga juga tidak memberikan dukunganTujuan: Untuk menganalisis hubungan sosial budaya dan dukungan keluarga dengan keikutsertaan KB.Metode : Penelitian kuantitatif dengan pendekatan cross sectional. Penelitian dilakukan di wilayah Kerja Puskesmas Kota Datar yaitu di Desa Tandem Hulu I Kecamatan Hamparan Perak Kabupaten Deli Serdang. Populasi penelitian sebanyak 1.711 orang dan sampel diperoleh sebanyak 324 responden. Penarikan sampel secara acak sederhana (simple random sampling). Analisis data menggunakan analisis univariat, analisis bivariat dengan uji chi-square pada tingkat kepercayaan 95% (p<0,05).Hasil: Menunjukkan bahwa sosial budaya dan dukungan keluarga berhubungan dengan keikutsertaan KB di Wilayah kerja Puskesmas Kota Datar Desa Tandem Hulu I Kecamatan Hamparan Perak Kabupaten Deli Serdang, p < 0,05.Simpulan : Ibu yang tidak mendapat dukungan sosial budaya dan mendapatkan dukungan dari  keluarga cenderung menggunakan alat kontrasepsi, dan ibu yang mendapat dukungan sosial budaya dan tidak mendapatkan dukungan suami cenderung tidak menggunakan alat kontrasepsi.